Analisis Hambatan Berbicara Bahasa Arab Mahasiswi dalam Implementasi Bi’ah Lughawiyyah di Pesantren Berbasis Perguruan Tinggi - Ghumaisha; Mufarokah, Siti (EL-FUSHA: Jurnal Bahasa Arab dan Pendidikan, 2026)
Arabic speaking skills are one of the essential competencies required in a university-based Islamic boarding school environment that implements a language immersion program. However, in practice, female students still encounter various obstacles that affect the effectiveness of their use of Arabic in daily communication. This study aims to analyze the various obstacles faced by students in speaking Arabic within a university-based Islamic boarding school environment that implements a language immersion program. Although this environment is designed to encourage the active use of Arabic, in reality, many students still experience difficulties in oral communication. This study employs a qualitative approach using a descriptive-analytical method. Data were collected through observation, in-depth interviews, and documentation toward the students and language program administrators. The research results indicate that the obstacles faced fall into several main categories: linguistic, psychological, and environmental. Linguistically, limited vocabulary and weak command of language structure are the dominant factors. Psychologically, feelings of embarrassment, fear of making mistakes, and low self-confidence also hinder the willingness to speak. Meanwhile, from an environmental perspective, the lack of consistency in the use of Arabic in daily interactions, weak supervision, and the influence of the mother tongue are significant external factors. Additionally, it was found that the success of the language immersion program heavily depends on the synergy between institutional policies, the role of language instructors, and the individual motivation of the students. Therefore, comprehensive strategies are needed, such as enhancing language immersion programs, strengthening the role of language supervisors, and employing psychological approaches to boost students’ self-confidence. This study is expected to contribute to the development of a more effective Arabic language learning model within university-based Islamic boarding schools, particularly by creating a conducive and sustainable language environment.